2016
DOI: 10.1002/hipo.22608
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐cognitive action of CART is mediated via ERK in the hippocampus

Abstract: Although cocaine- and amphetamine-regulated transcript peptide (CART) is detected in several cortical and subcortical areas, its role in higher functions has been largely ignored. We examined the significance of CART in memory formation and tested if the downstream actions of CART involve N-methyl-d-aspartate (NMDA) activated extra-cellular signal-regulated kinase (ERK). Newly formed memory was evaluated using novel object recognition test consisting of familiarization (T1) and choice trials (T2). The choice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Recent study from our laboratory showed that neural circuit across entorhinal cortex, perirhinal cortex and hippocampus may play an important role in recognition memory (Bharne et al . ). The study revealed that CART promotes long‐term memory within the framework of hippocampus and may engage NMDA‐ERK signaling.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Recent study from our laboratory showed that neural circuit across entorhinal cortex, perirhinal cortex and hippocampus may play an important role in recognition memory (Bharne et al . ). The study revealed that CART promotes long‐term memory within the framework of hippocampus and may engage NMDA‐ERK signaling.…”
Section: Discussionmentioning
confidence: 97%
“…Exploration time for each object was recorded along with the discrimination index (DI) calculated as, DI = (N − F)/(N + F), representing difference in exploration time expressed as a proportion of the total time spent exploring the two objects in testing phase (Ennaceur & Delacour ; Bharne et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations